Influência dos parâmetros térmicos de solidificação na transição colunar/equiaxial em ligas do sistema Sn-Pb sob condições transitórias de extração de calor - MOUTINHO, Daniel Joaquim da Conceição (Universidade Federal do Pará, 2014)
This work carry out a theoretical experimental study about the influence of solidification thermal parameters on the columnar to equiaxed transition of Sn 5%Pb, Sn 15%Pb, and Sn 20% Pb and Sn 25% Pb alloys during the horizontal unidirectional solidification process cooled by water which considers the solute convection effects. The tip growth rates and cooling rates have been experimentally calculated and the obtained results are compared with those of a numerical model. The columnar to equiaxed transition position is determined through the macrostructure characterization of the studied alloys. The experimental results have shown that the thermosolutal convection influences the CET occurrence. Finally, a comparative experimental study is done for the studied alloys when directionally solidified in different water-cooled systems.